2018
DOI: 10.1016/j.virusres.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Porcine deltacoronavirus induces caspase-dependent apoptosis through activation of the cytochrome c-mediated intrinsic mitochondrial pathway

Abstract: Porcine deltacoronavirus (PDCoV), a newly discovered enteric coronavirus, is a causative agent of severe clinical diarrhea and intestinal pathological damage in piglets. As a first step toward understanding the effect of PDCoV on host cells, we elucidated mechanisms underlying the process of apoptotic cell death after PDCoV infection. The use of a pan-caspase inhibitor resulted in the inhibition of PDCoV-induced apoptosis and reduction of PDCoV replication, suggestive of the association of a caspase-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 51 publications
2
50
2
Order By: Relevance
“…Apart from its pivotal roles in virus entry and replication, virusinduced Ca 2+ oscillation also regulates other biological processes, such as ER stress, apoptosis and autophagy. Previous studies suggested that PDCoV infection induces apoptosis in swine testicular and LLC-PK1 cells, possibly through the activation of the cytochrome c-mediated intrinsic mitochondrial pathway (Jung et al, 2016;Lee and Lee, 2018). A recent study also showed that PDCoV infection induces autophagosome-like vesicles associated with increased autophagic activity (Qin et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Apart from its pivotal roles in virus entry and replication, virusinduced Ca 2+ oscillation also regulates other biological processes, such as ER stress, apoptosis and autophagy. Previous studies suggested that PDCoV infection induces apoptosis in swine testicular and LLC-PK1 cells, possibly through the activation of the cytochrome c-mediated intrinsic mitochondrial pathway (Jung et al, 2016;Lee and Lee, 2018). A recent study also showed that PDCoV infection induces autophagosome-like vesicles associated with increased autophagic activity (Qin et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…When PARP cleavage in SADS-CoV-infected cells was blocked, SADS-CoV infection was dramatically inhibited. These findings suggested that apoptosis is required for the replication of SADS-CoV as shown in PDCoV [12]. Thus, the caspase-dependent apoptotic pathway seems to be manipulated by SADS-CoV to ensure competent viral replication in target cells.…”
Section: Discussionmentioning
confidence: 90%
“…However, some viruses induce apoptosis to facilitate the release and dissemination of viral progeny for further invasion, which are important biological activities in viral pathogenesis and disease processes that promote cell death and tissue injury. Recent studies have demonstrated the ability of numerous coronaviruses to elicit or inhibit apoptosis either directly or indirectly during their replication cycles such as transmissible gastroenteritis virus (TGEV) [10,35], avian infectious bronchitis virus (IBV) [36], mouse hepatitis virus (MHV) [37], porcine deltacoronavirus (PDCoV) [12], and porcine epidemic diarrhea virus (PEDV) [11]. Although various viruses are known to modulate apoptosis as a critical armament to complete their replication cycle, whether SADS-CoV induces apoptosis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase-8 is an initiator caspase, with the released active dimer known to cleave a variety of downstream targets, including the executioner caspase, caspase-3 (Keller et al, 2018). Caspase-3 is activated by both extrinsic and intrinsic apoptotic pathways, and is responsible for the morphological features of apoptosis (Lee and Lee, 2018). Apoptotic factors caspase-3 and caspase-8 are up-regulated during PEDV infection, especially in the later stages (Ming-Ming et al, 2014).…”
Section: Discussionmentioning
confidence: 99%